2014
DOI: 10.1016/j.celrep.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Dual Engagement of the NLRP3 and AIM2 Inflammasomes by Plasmodium-Derived Hemozoin and DNA during Malaria

Abstract: SUMMARY Hemozoin (Hz) is the crystalline detoxification product of hemoglobin in plasmodial-infected erythrocytes. We previously proposed that Hz can carry plasmodial DNA into a subcellular compartment accessible to Toll-like receptor 9 (TLR9), inducing an inflammatory signal. Hemozoin also activates the NLRP3 inflammasome in primed cells. We found that Hz appears to co localize with DNA in infected erythrocytes, even prior to RBC rupture or phagolysosomal digestion. Using synthetic Hz coated in vitro with pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
165
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(191 citation statements)
references
References 55 publications
7
165
0
9
Order By: Relevance
“…Kupfer cells) are always in a primed state. Indeed, we (45) have observed that the liver of otherwise untreated mice expresses pro-IL-1 ␤ in abundance, and that this pro-IL1 ␤ is processed to the active form upon appropriate stimulation. It is likely that human patients who take oral statins for hypercholesterolemia can generate the 28-kDa IL-1 ␤ intermediate without the need for additional priming stimuli on this basis.…”
Section: Discussionmentioning
confidence: 99%
“…Kupfer cells) are always in a primed state. Indeed, we (45) have observed that the liver of otherwise untreated mice expresses pro-IL-1 ␤ in abundance, and that this pro-IL1 ␤ is processed to the active form upon appropriate stimulation. It is likely that human patients who take oral statins for hypercholesterolemia can generate the 28-kDa IL-1 ␤ intermediate without the need for additional priming stimuli on this basis.…”
Section: Discussionmentioning
confidence: 99%
“…6 NLRP3 inflammasome is activated by a diverse set of stimuli, but, classically, it is associated to the sensing of noxious agents as monosodium urate crystals (associated to gout) and extracellular ATP, particles as silica and asbestos, and also pathogens. 7 Among infectious agents, bacteria, as Streptococcus agalactiae 8 ; viruses, as Rift Valley fever virus 9 ; protozoans, as Plasmodium berghei 10 and fungi, as Candida albicans 11 were shown to activate this system. This multitude of potential activators places NLRP3 as a prominent actor in many diseases associated to inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The requirement for dual sensing of pathogens by both AIM2 and NLRP3 has also been observed in mouse bone marrow-derived macrophages stimulated with Plasmodium berghei ANKA infected redblood cells (Kalantari et al, 2014). There is evidence that A. fumigatus genomic DNA, transfected into the cell cytoplasm as well as for the Plasmodium falciparum genomic DNA, transported into the cytoplasm by hemozoin are recognized by AIM2 directly (Kalantari et al, 2014;Karki et al, 2015). Further studies to elucidate the mechanisms involved are warranted.…”
Section: The Duality Of Aim2: An Overviewmentioning
confidence: 98%
“…Additional to bacteria and viruses AIM2 mediates pathogen recognition of and host defense to the fungal pathogen Aspergillus fumigatus and the Plasmodium berghei ANKA (Karki et al, 2015;Kalantari et al, 2014). It has been shown, that mice lacking both AIM2 and NLRP3, ASC or caspase-1 and infected with A. fumigatus are more susceptible than infected WT (Karki et al, 2015).…”
Section: The Duality Of Aim2: An Overviewmentioning
confidence: 99%